Odpowiedzi

Najlepsza Odpowiedź!
2010-01-16T15:09:33+01:00
A)-4x-7-3x+7 = -7x
b)x-2xy+1/2x-1/3xy = 1,5x-2 1/3xy
c)-x²+y²-2x²-1/3xy = -x²+y²-1/3xy
d)-x²+2x-3x+x² = -x
e)4x+4-7x-1/2 = -3x+3 1/2
f)-2ab+12a-4ab-16a=-6ab-4a
1 5 1
2010-01-16T15:10:18+01:00
A)-4x-7-3x+7 = -7x
b)x-2xy+1/2x-1/3xy = 1½x - 2⅓xy
c)-x²+y²-2x²-1/3xy = -3x² - ⅓xy +y²
d)-x²+2x-3x+x² = -x
e)4x+4-7x-1/2 = -3x + 3½
f)-2ab+12a-4ab-16a = -4a -6ab
1 5 1
2010-01-16T15:10:33+01:00
A)-7
b)1 1/2 x (jeden i jedna druga x) - 2 1/3 xy (dwa i jedna trzecia xy)
c) -3x² +y²- 1/3 xy²
d)-x
e)-3x + 3 1/2 (trzy i jedna druga
f)2ab =-4a
1 5 1